(untitled) (Research, Society and Development, 2022)
The objective of this study was to evaluate, by means of computer simulation, the difference in mechanical strength between two plate models straight and wave used in femur fracture fixation, submitting both to a progressive static axial load. There are criteria to evaluate the yield strength of a material: Tresca, Von Mises and Mohr-Coulomb. In this study, the Von-Mises strain criterion theory was used because it is used in fatigue strength tests of ductile materials, in this case, stainless steel. This criterion, indicates that the yielding of a solid material begins when it reaches a critical stress value. The models were built computationally using 3D modeling software. The finite element mathematical method was used to evaluate the stress and strain curve, two elements considered fundamental to verify the behavior of the metal during the application of stress and the displacement of the plates, to thus evaluate the strength of each. The results obtained after the finite element analysis show that the plates do not reach the critical limit for yielding, but the straight plate absorbs 10 times more stress compared to the wave plate. The wave plate allows the conclusion that there is decomposition of the applied force. Both plates remain in the elastic regime with load up to 1000 N. The load is equivalent to the weight of the body and gravity. It was concluded that the axial force applied in the caudal direction decomposes into resulting ones compared to the straight plate, which absorbs all the load and may reach the critical limit for yielding before the wave plate.